Toxicity Study On Siddha Formulation Mega Sanjeevi Mathirai In Albino Rats - SATHISH.R; J. ANBU; M. MURGESAN; ASHWINI ANJANA; ARUN KUMAR (International Journal of Pharma and Bio Sciences, 2012)
The present study was carried out to investigate the toxicity of Siddha formulation Mega Sanjeevi Mathirai in albino rats. The animals were maintained on a standard laboratory conditions. Acute toxicity study and repeated dose oral toxicity study was done on different dose levels. The experiments were carried out in four groups of animals. Each group contains 6 animals. Among them were 3 males and 3 females. Histopathological studies, hematological investigations, biochemical parameters and ICP-OES studies were done to find out abnormality if any. LD50 cut off value was calculated. The safe dose of Mega Sanjeevi Mathirai was recommended to be 100mg/kg or less than 200 mg/kg body weight.